Becoming Medical Personnels during Colonial Java: Historical Reflection on the Experience and Struggle of Women - Ningrum, Siti Utami Dewi; Ali, Makrus (Yayasan Jurnal Perempuan, 2016)
The number of women in the medical field today is probably much evolved compared to when this science was first introduced in Indonesia. In the colonial period, the number of women entering into the medical field was minimal. Patriarchal values restricted women’s access to education, including the education of doctors, nurses, midwives and pharmacists. Becoming a doctor was considered to be against women’s ‘nature’. The STOVIA medical school at the turn of the 20th century, for example, was discriminatory towards women. The medical profession was seen as suitable only for men. Using a historical perspective, this study seeks to uncover the experience womens in the medical field in Indonesia. The achievements of women to date were inspired by the struggles of thewomen in the past.